Assessing the precision of strain measurements using electron backscatter diffraction - part 1: Detector assessment - Britton, T; Jiang, J; Clough, R; Tarleton, E; Kirkland, A; Wilkinson, A (2013)
We analyse the link between precision of pattern shift measurements and the resolution of the measurement of elastic strain and lattice rotation using high resolution electron backscatter diffraction (HR-EBSD). This study combines analysis of high quality experimentally obtained diffraction patterns from single crystal silicon; high quality dynamical simulations using Bloch wave theory; quantitative measurements of the detector Modulation Transfer Function (MTF) and a numerical model. We have found that increases in exposure time, when 1×1 binning is selected, are the primary reason for the observed increase in sensitivity at greater than 2×2 binning and therefore use of software integration and high bit depth images enables a significant increase in strain resolution. This has been confirmed using simulated diffraction patterns which provide evidence that the ultimate theoretical resolution of the cross correlation based EBSD strain measurement technique with a 1000×1000 pixel image could be as low as 4.2×10-7 in strain based on a shift precision of 0.001 pixels. © 2013 Elsevier B.V.